The Use of Numerals in the First Extensive Historical Work in Slovene - Ulčnik, Natalija (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
The article discusses the use of numerals in the first historical work in Slovene, i.e. Anton Krempl’s Dogodivšine štajerske zemle (The History of the Land of Styria) published in 1845. The research focuses on how numerals are included in the text and on the occurrence of individual types of numerals in connection with their intended use in the text. The article also highlights the linguistic characteristics of the numerals used, particularly in comparison to contemporary grammatical examples and to references in Pleteršnik’s dictionary.